Validity and reliability of a depression, anxiety and stress scale in Cuban dental students during the COVID-19 - José Daniel Villegas-Maestre; Elys María Pedraza-Rodríguez; Ibraín Enrique Corrales-Reyes; Renzo Felipe Carranza-Esteban; Oscar Javier Mamani-Benito (Editorial Ciencias Médicas, 2023)
Introduction: An indisputable consequence has to do with the psychological impact of the COVID-19 on health professionalsand students. In Cuba, these psychological manifestations have scarcely been investigated, and there are no reports in the dental undergraduate program. Objective: To analyze the evidences of validity and reliability of a depression, anxiety and stress scale in Cuban dental students in the context of COVID-19. Methods: An instrumental and cross-sectional study was carried out, which included students of all years and Cuban universities. A documentary measurement instrument was validated, using its main psychometric evidence. Convergent validity was analyzed and reliability was estimated using Cronbach's alpha coefficient. Results: 301 students were included, of which 74.09 % were women and whose ages ranged from 17 to 30 years. The asymmetry and kurtosis values of all items were adequate. The confirmatory factorial analysis showed that the factorial structure of 21 items distributed in 3 factors is satisfactory. The goodness of fit indices was equally satisfactory. The scale factors are directly and significantly related with the Generalized Anxiety Disorder-2 (p<0.01) and the Patient Health Questionnaire-2 (p<0.01); the scale shows evidences of convergent validity. With Cronbach's α coefficient, the scale scores were estimated to be reliable. Conclusions: The depression, anxiety and stress scale (DASS-21) in Cuban dental students in the context of COVID-19 turned out to be valid and reliable, in addition to allowing the evaluation of the dimensions of these three factors in this sector of the society.